On “Unspoken Language of Things” Basic Grammatical Features of Mesoamerican Languages Bilingual Version - Lara-Martínez, Rafael (2026)
“The Unspoken Language of Things” presents “twenty (20) basic grammatical features of Mesoamerican languages” to a Salvadoran audience. Since almost all universities exclude the study of Native linguistics from their curriculum, only foreign research provides accurate data on ancestral mother tongues, except for current Nahuat revitalization. Whether it is the idea of a Latin American philosophy, as well as the concept of decolonization, a dialogue between these disciplines and linguistics seems impossible. If history repeats that forgetting denies the past and complicates future projects, languages do not play a role in its reflection of national events, not even in “silent” indigenous revolts. In a similar way, literature constructs a monolingual canon that eliminates most of the ancestral poetics, replaced by prestigious foreign tongues, i.e., Quiché, Yucatec, Nahuatl, etc. The essay focuses on twenty basic grammatical features to include a clear contrast with the official national language, conceived as the only one capable of translating the world into words. We must question the critical roots of nationalist identity without a dialogue with its own linguistic history. Language is located at the vertex of a notional triangle by linking the right to communal lands withancient culture, now renovated.